SISTEM INFORMASI PENJUALAN ONLINE SAUS DAN SAMBEL EXPRESS - Siti Ngatijah; Syahriani Syahriani; Tri Santoso (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
The data processing system is one of the functions of administrative activities in providing services to customers and to meet any information demands of the manager. A good information system can always solve problems that occur and can produce fast, precise, and accurate information. The computer is a tool for producing the right information with access to human work. In the midst of this technological development is to analyze and design a system of selling sauce and chili sauce. This system is made to make it easier for office staff to check incoming orders and make it easy for customers to order goods. Problems often occur, namely the lack of information for incoming orders. The method used for data collection is analysis (by surveys, interviews and literature studies). The result of this research is a sales system that can be used by office staff and managers during working hours. Can improve efficiency in activities so that the service is better than the previous system. The conclusion is that this system has designs such as product names, purchase confirmations, customer lists and stock items.